Controlled growth of MoS2 by atomic layer deposition on patterned gold pads - Yue, Chenxi; Wang, Yang; Liu, Hao; Chen, Lin; Zhu, Hao; Sun, Qingqing (Journal of crystal growth, 2020)
•ALD-based synthesis approach was developed for the deposition of MoS2.•Growth behaviors on various substrates were analyzed and compared.•Mechanism of MoS2 growth on Au by ALD was discussed.•Selective growth of MoS2 at controlled location was achieved using ALD. Approaches to synthesize large-area MoS2 thin films have been extensively investigated in recent years towards system-level micro-/nanoelectronics applications. Methods including chemical vapor deposition (CVD) and atomic layer deposition (ALD) can enable uniform and wafer-scale MoS2 films on insulating substrates, but without selective control on the growth location. Herein, we report a controlled growth of ultra-thin MoS2 films on Au pads patterned on insulating substrates using ALD-based techniques. Clear difference in the incubation period duration of the ALD process among different substrate surfaces has been observed. Selective growth of MoS2 can be achieved on patterned Au on SiO2/Si substrate while the incubation period is shorter on sapphire substrate as compared with that on SiO2/Si. In addition, the influence of deposition temperature on the film growth dynamics on difference surfaces has been studied. Such controlled growth of MoS2 by ALD can be very attractive in future optoelectronics applications and the synthesis on patterned Au is promising in fulfilling its application potentials such as electrocatalyst in hydrogen evolution reaction.